The Effectiveness Of The Project-Based Learning Model on Student Creativity: A Literature Review (2014–2023) - Windy Zaerani; Sheliana Iqlima; Gunawan Gunawan (Indonesian, 2024)
This study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model in enhancing student creativity across various educational levels and disciplines based on empirical research published between 2014 and 2023. Using the Systematic Literature Review (SLR) method, ten highly relevant articles were selected and analyzed. The results of the synthesis indicate that the implementation of PjBL has a positive and significant impact on students' creativity, particularly in aspects of fluency, flexibility, originality, and elaboration. The integration of digital technology, virtual media, and innovative pedagogical approaches (such as STEM) further accelerates the acquisition of creative skills. Additionally, PjBL fosters active learning environments and cognitive achievement, showing a strong interaction with students' initial creativity levels. The findings suggest that PjBL is a robust and adaptive instructional framework suitable for meeting 21st-century educational demands. Future research should focus on longitudinal assessments and larger scale implementations to generalise these positive outcomes across diverse cultural and socio-economic learning contexts.